Roadside drug testing: An evaluation of the Alere DDS®2 mobile test system. Issue 4 (9th November 2017) - Rohrig, Timothy P.; Moore, Christine M.; Stephens, Kimberly; Cooper, Kelsey; Coulter, Cynthia; Baird, Tyson; Garnier, Margaux; Miller, Samuel; Tuyay, James; Osawa, Kei; Chou, Joshua; Nuss, Carson; et al.
Abstract: The number of drivers using drugs has increased over the last few years, and is likely to continue its upward trend. Testing drivers for alcohol use is routine and standardized, but the same is not true for the identification of driving under the influence of drugs (DUID). The Drug Evaluation and Classification Program (DECP) was developed to train police officers to recognize the signs and symptoms of recent drug use and remains an invaluable program; however, there are insufficient numbers of these highly trained drug recognition experts (DREs) available to attend every potential drug involved traffic incident. While blood and urine samples are used to test for drugs in a driver, both have disadvantages, particularly as they pertain to the length of time required after a traffic stop to sample collection. Therefore, the development of oral fluid testing devices which can be operated at the roadside and have the potential to assist officers in the identification of drug use is a major advancement in DUID cases. This project evaluated the performance of one instrumental oral fluid roadside testing device (Alere DDS®2) compared to DRE opinion, oral fluid laboratory‐based analysis, and routine blood testing. The results showed that there was a good correlation with DRE observations and the device performance was >80% in all drug categories compared to laboratory‐based analytical testing, both in oral fluid and blood, with few exceptions. The instrument can be considered a useful tool to assist law enforcement in identifying a drugged driver. Because the device does not test for all potentially impairing drugs, the opinion of the police officer regarding the condition of the driver should still be considered the most important aspect for arrest and further action. Abstract : The Alere DDS®2 mobile roadside drug testing system was evaluated as a presumptive screening device for drugs in oral fluid. All control subjects tested negatively and the corresponding oral fluid and blood samples analyzed in the laboratories were confirmed as negative; there was a good correlation with DRE observations and the device performance was >80% in all drug categories compared to laboratory‐based analytical testing; both in oral fluid and blood, with few exceptions.